2009
DOI: 10.1016/j.jhealeco.2008.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Are mature smokers misinformed?

Abstract: While there are many reasons to continue to smoke in spite of its consequences for health, the concern that many smoke because they misperceive the risks of smoking remains a focus of public discussion and motivates tobacco control policies and litigation. In this paper we investigate the relative accuracy of mature smokers' risk perceptions about future survival, and a range of morbidities and disabilities. Using data from the Survey on Smoking (SOS) conducted for this research, we compare subjective beliefs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“… 9 See, however, Khwaja, Silverman & Sloan (2007) for the view that smokers accurately estimate their survival chances. …”
mentioning
confidence: 99%
“… 9 See, however, Khwaja, Silverman & Sloan (2007) for the view that smokers accurately estimate their survival chances. …”
mentioning
confidence: 99%
“…In the sample as a decades, to the dissemination of information in the mass media. (9,16) One study that investigated the knowledge regarding the risk factors (smoking, drinking excessive alcohol, having a sedentary lifestyle and eating an unhealthy diet) for the development of cancer and heart diseases showed that more than 60% of the population studied recognized only smoking as a risk factor. However, there are still myths regarding the individual risk for the development of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…There is empirical evidence indicating that, if anything, smokers overestimate the probability that smoking will lead to adverse health outcomes and death Costa-Font and Rovira 2005;Khwaja et al 2009;Liu and Hsieh 1995;Viscusi 1990;1991;Viscusi et al 2000). Most of this evidence, however, which directly elicits probabilities of adverse health outcomes is for persons much older than the age at which the smoking habit is typically initiated.…”
Section: Previous Literaturementioning
confidence: 99%
“…However, Hanson and Logue's argument was based on a conjecture which lacks empirical support. For example, Khwaja et al (2009), in an analysis of responses of older persons to subjective probability questions about mortality, report no meaningful difference in responses when the question is phrased in the third versus the second person. 9 Economic evidence on individuals' over-optimism is mixed.…”
Section: Previous Literaturementioning
confidence: 99%